Removal of copper ions by few‐layered graphene oxide nanosheets from aqueous solutions: external influences and adsorption mechanisms. Issue 8 (25th March 2018) - Wang, Hui; Hu, Xinjiang; Guo, Yuan; Qiu, Caisheng; Long, Songhua; Hao, Dongmei; Cai, Xiaoxi; Xu, Wenwen; Wang, Yufu; Liu, Yunguo
Abstract: BACKGROUD: In this work, graphene oxide (GO) was synthesized followed by a modified Hummers method and several characterization techniques were provided. Its adsorptive activity was evaluated based on the removal of Cu(II) from an aqueous solution. External influences were taken into account to further study the adsorption mechanism. RESULT: Characterization results revealed that GO was well prepared and a large amount of oxygen‐containing functional groups were introduced. The Cu(II) adsorption increased with increasing solution pH and precipitate at alkaline conditions. NaCl concentration improved copper adsorption at low pH. Formate reduced copper adsorption while benzoate improved the adsorption under low pH conditions. CONCLUSIONS: Here, GO performed Cu(II) adsorption well. The external conditions have different influences on the adsorption process. Experimental results demonstrate that GO is a promising alternative material for pollutants removal. © 2018 Society of Chemical Industry